Minimalist video-assisted thoracic surgery biopsy of mediastinal tumors - Tacconi, Federico; Rogliani, Paola; Cristino, Benedetto; Gilardi, Francesco; Palombi, Leonardo; Pompeo, Eugenio; Surgery Research, for the Awake Thoracic (Journal of Thoracic Disease; Vol 8, No 12 (December 31, 2016): Journal of Thoracic Disease, 2016)
Background: Mediastinal tumors often require surgical biopsy to achieve a precise and rapid diagnosis. However, subjects with mediastinal tumors may be unfit for general anesthesia, particularly when compression of major vessels or airways does occur. We tested the applicability in this setting of a minimalist (M) uniportal, video-assisted thoracic surgery (VATS) strategy carried out under locoregional anesthesia in awake patients (MVATS). Methods: We analyzed in a comparative fashion including propensity score matching, data from a prospectively collected database of patients who were offered surgical biopsy for mediastinal tumors through either MVATS or standard VATS. Tested outcome measures included feasibility, diagnostic yield, and morbidity. Results: A total of 24 procedures were performed through MVATS. Diagnostic yield was 100%. Median hospital stay and time interval to oncologic treatment were 2 days (IQR, 2–3 days) and 7 days (IQR, 5.5–11.5 days), respectively. At overall comparison (MVATS, N=24 vs. VATS, N=23), there was a significant difference in both frequency and severity of postoperative complication as measured by Clavien-Dindo classification (P